2018
DOI: 10.3389/fphys.2018.00191
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Transposition Surgery Decreases Fat Mass and Improves Glucose Metabolism in Diabetic GK Rats: Possible Involvement of FGF21

Abstract: Objective: Ileal transposition (IT) surgery has been reported to improve glucose and lipid metabolism, and fibroblast growth factor 21 (FGF21) is a powerful metabolic regulator. In the present study, we aimed to investigate the effects of IT surgery on metabolism and its possible relationship with the FGF21 signaling pathway in diabetic Goto-Kakizaki (GK) rats.Methods: Ten-week-old male GK rats were subjected to IT surgery with translocation of a 10 cm ileal segment to the proximal jejunum (IT group) or sham s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…These conflicting results with RYGB is probably associated with its complicated weight-loss mechanism, including restricted gastric volume, altered intestine structure, and significant changes in gut hormone levels. Interestingly, the decrease in FGF21 level was also reported in other two forms of bariatric surgeries, namely, duodenal-jejunal omega switch (DJOS) that bypasses the entire duodenum and proximal jejunum (41), and ileal transposition (IT), a classic bariatric surgery with the transposition of a distal ileum segment to the proximal jejunum (42). All the four surgical techniques mentioned above (DJB, RYGB, DJOS, and IT) include the rearrangement of the small intestine.…”
Section: Discussionmentioning
confidence: 66%
“…These conflicting results with RYGB is probably associated with its complicated weight-loss mechanism, including restricted gastric volume, altered intestine structure, and significant changes in gut hormone levels. Interestingly, the decrease in FGF21 level was also reported in other two forms of bariatric surgeries, namely, duodenal-jejunal omega switch (DJOS) that bypasses the entire duodenum and proximal jejunum (41), and ileal transposition (IT), a classic bariatric surgery with the transposition of a distal ileum segment to the proximal jejunum (42). All the four surgical techniques mentioned above (DJB, RYGB, DJOS, and IT) include the rearrangement of the small intestine.…”
Section: Discussionmentioning
confidence: 66%
“…A portion of sWAT was fixed in 10% formalin. Histological analysis and the adipocyte size of sWAT were measured, as described previously 31 . Serum fasting blood glucose of mice was measured by routine automated laboratory methods.…”
Section: Samples Collection and Biochemical Measurementsmentioning
confidence: 99%
“…A study by Yan et al . on GK rats also showed reduced body weight, fat mass, and food intake, improved glucose metabolism, and increased insulin sensitivity after IT procedure 46 . On the other hand, other IT studies carried out on Zucker rats 43 , 47 and UCD-T2DM rats 48 revealed no impact of IT procedure on body weight.…”
Section: Discussionmentioning
confidence: 82%